Design of Android-based Online Ticketing System Application on Hiba Utama Bus Using Location Based Service (LBS) - Styoko, Dwi; Faizah, NM; Koryanto, Lucky (Journal Mobile Technologies (JMS), 2023)
Hiba Utama buses still use conventional methods in ordering tickets and searching for the departure schedule of a prospective passenger, namely through outlets/counters and via telephone only. This method is less effective both in terms of time and cost because there can be a discrepancy between the customer's wishes in terms of departure time or even the tickets have sold out. So that information applications and ordering bus tickets are needed that can provide clear information and are not limited by distance and time by using mobile media. This study aims to build information applications and order bus tickets based on Android. The application development stage includes analysis, system design, implementation, and testing. Methods of data collection using the method of literature study, and observation. Android-based bus ticket information and booking applications built with the Java programming language. Android-based bus ticket information and booking applications that are made to provide bus information and ticket bookings. So that it can make it easier for customers to access information and order bus tickets due to the level of effectiveness and efficiency of the function of the mobile itself. The results of system testing show that this application is feasible and can be used as a tool to provide information and to order Hiba Utama bus tickets.